2008
DOI: 10.1016/j.steroids.2008.04.006
|View full text |Cite
|
Sign up to set email alerts
|

ERβ in breast cancer—Onlooker, passive player, or active protector?

Abstract: The role of estrogen exposure in breast cancer risk is well-documented, and both estrogen synthesis and actions through the estrogen receptor (ER) have been targeted by therapies to control hormonedependent breast cancer. The discovery of a second ER form and its therapeutic implications sparked great interest. Both the original ERα and the more recently identified ERβ subtypes bind and respond similarly to many physiological and pharmacological ligands. However, differences in phytoestrogen binding have been … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
121
1
6

Year Published

2009
2009
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 152 publications
(137 citation statements)
references
References 119 publications
(293 reference statements)
6
121
1
6
Order By: Relevance
“…42,43 We asked whether this is also the case in our system, and investigated whether this affects cellular response to lapatinib. To this end, we transiently transfected SK-BR-3 cells with ERβ1-or ERβ2-expressing vectors, and treated them with 0.1 μM lapatinib for 48 h. We found that ERβ1 expression inhibited cell proliferation and enhanced G 1 cell cycle arrest, both in the presence and absence of lapatinib ( Fig.…”
Section: Lapatinib Induces P27 Phosphorylation At Serine10 and Inhibimentioning
confidence: 99%
“…42,43 We asked whether this is also the case in our system, and investigated whether this affects cellular response to lapatinib. To this end, we transiently transfected SK-BR-3 cells with ERβ1-or ERβ2-expressing vectors, and treated them with 0.1 μM lapatinib for 48 h. We found that ERβ1 expression inhibited cell proliferation and enhanced G 1 cell cycle arrest, both in the presence and absence of lapatinib ( Fig.…”
Section: Lapatinib Induces P27 Phosphorylation At Serine10 and Inhibimentioning
confidence: 99%
“…In particular, one critical discovery has been the identification of a second estrogen receptor (ER), called ERb (Kuiper et al 1996), in contrast to the classical ERa, which can also mediate estrogen action in target cells. The discovery of ERb has led to a full reevaluation of estrogen action in all target tissues, including human breast cancer (Fox et al 2008). However, despite over 15 years of research, the exact role, if any, played by ERb in human breast cancer remains elusive (Fox et al 2008, Thomas & Gustafsson 2011, Murphy & Leygue 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Both monomeric forms of each receptor subtype are approximately 60 kDa and both subtypes bind estradiol-17 with high affinity but differ in DNA-binding affinity. These two ER subtypes are capable of mediating different functions depending on the nature of bound ligands, post-translational modifications, cofactor interactions and promoter response elements (2,3). The expression and functions of the two ER subtypes in placenta were previously confirmed.…”
Section: Introductionmentioning
confidence: 90%